2013
DOI: 10.3855/jidc.2805
|View full text |Cite
|
Sign up to set email alerts
|

Successful switch to oral therapy with doxycycline in the case of an actinomycotic hepatic abscess

Abstract: A 72-year-old female was admitted with the symptoms of malaise, loss of appetite, upper right quadrant pain, fever, and sweats, which had been present for last 7 days. CT-scan of the abdomen revealed a hypodense mass in the right liver lobe; histopathological examination of the biopsy specimen yielded a diagnosis of actinomycotic abscess. Treatment with intravenous ampicillin for 8 weeks followed by a course of oral doxicycline for 28 weeks resulted in the complete resolution of the abscess.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Fistulas to the skin (through the abdominal wall), the bronchial tree, the lung, and the pericardial space were described in a limited number of cases [9,13,39,62,87]. Rare complications included thrombosis or obstruction of the portal vein (n = 8) [29,43,45,[88][89][90][91], hepatic vein thrombosis (n = 3) [23,49,80] and inferior vena cava thrombosis or obstruction (n = 2) [23,81], cardiac tamponade (n = 3) [28,92,93], and gastrointestinal bleed (n = 1) [94].…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Fistulas to the skin (through the abdominal wall), the bronchial tree, the lung, and the pericardial space were described in a limited number of cases [9,13,39,62,87]. Rare complications included thrombosis or obstruction of the portal vein (n = 8) [29,43,45,[88][89][90][91], hepatic vein thrombosis (n = 3) [23,49,80] and inferior vena cava thrombosis or obstruction (n = 2) [23,81], cardiac tamponade (n = 3) [28,92,93], and gastrointestinal bleed (n = 1) [94].…”
Section: Review Of the Literaturementioning
confidence: 99%
“…PHA occurs worldwide, but only 87 cases were reported in English literature between 1966 and 2015; none of them were from mainland China. This case prompted us to review PHA cases reported from mainland China in Chinese literature, and share the experience with the colleagues in the rest of the world.…”
mentioning
confidence: 99%